PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT BANK NEGARA INDONESIA (PERSERO) TBK BATAM - Rikky (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
This study aimed to determine the impact of PT Bank Negara Indonesia (Persero) Tbk Batam’s facilities, service quality and trust on customer satisfaction. There is no doubt that facilities, service quality and trust are factors that can affect on customer satisfaction. By improving the facilities, service quality and trust will have a positive impact on customer satisfaction. The sample of the study identified 249 PT Bank Negara Indonesia (Persero) Tbk Batam’s customers. The way to gather information for research is by distributing questionnaires to customers. The data analysis methods of diagnostic tools, which include validity tests, reliability tests, standardized assumptions, and hypothesis tests including T-test and F-test. The research tool used to process and analyze this analytical data was SPSS version 25.0. The results of the study indicate that facilities have a positive and significant impact on customer satisfaction. Service quality hasn’t significant impact on customer satisfaction. At the same time facilities and service quality are very effective in improving customer satisfaction.